An Investigation on Flame Shape and Size for a High-Pressure Turbulent Non-Premixed Swirl Combustion - Zhongya Xi; Zhongguang Fu; Xiaotian Hu; Syed Waqas Sabir; Yibo Jiang (Energies, 2018)
Flame shape and size for a high-pressure turbulent non-premixed swirl combustion were experimentally investigated over a wide range of varying parameters including fuel mass flow rate, combustor pressure, primary-air mass flow rate, and nozzle exit velocity. A CFD simulation was conducted to predict the flame profile. Meanwhile, a theoretical calculation was also performed to estimate flame length. It was observed that flame length increased linearly with increasing fuel mass flow rate but decreased with the increment of combustor pressure in the power function. The flame diminished at a larger primary-air mass flow rate but remained unaffected by the increasing nozzle exit velocity. Considering the global effect of all parameters at a particular pressure, the flame length generally decreased as the primary-air to fuel ratio increased. This was attributed to the reduced air entrainment required to dilute the fuel to stoichiometric proportions. The CFD simulation offered a good prediction of the variation trends of flame length, although some deviations from experimental values were observed. The theoretical calculation estimated the trends of flame length variation particularly well. Nevertheless the difference between the theoretical and experimental results was found to be due to the swirl influence. Hence, a swirl factor was proposed to be added to the original equation for swirl flames.